The Effect of Encyclopedia and Discovery Learning to Improve Learning Motivation and Mastery of Concepts in Student - Anggraeni, Neli Dwi Septi; Octavia, Bernadetta (FKIP Universitas Lampung, 2023)
The Effect of Encyclopedia and Discovery Learning to Improve Learning Motivation and Mastery of Concepts in Student. Objectives: This study aims to determine effectiveness of encyclopedia structure function of plant tissue and discovery learning to increase learning motivation and mastery of concepts in grade XI MA. Methods: Techniques of data collection in learning motivation with questionnaires and mastery of concepts using tests. Tests and questionnaires were collected twice, namely pretest and posttest. The data obtained carried out prerequisite test analysis with normality and homogeneity test. Furthermore, paired t-test with SPPS V.15. Findings: The results of statistical analysis showed that P-value<0.05 that the encyclopedia structure function of plant tissue and discovery learning was effective in increasing student learning motivation and increasing mastery of concepts in grade XI MA. Conclusion: Effectiveness of encyclopedia structure function of plant tissue and discovery learning can improve learning motivation with effective categories and effectiveness of encyclopedia structure function of plant tissue and discovery learning can improve mastery of concepts with effective categories. Keywords: discovery learning, encyclopedia, learning motivation, mastery of concepts.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202334